Daya Tumbuh Stek Asystasia gangetica (L.) T. Anderson yang Disimpan pada Kondisi yang Berbeda: Viability of Asystasia gangetica (L.) T. Anderson Cutting Stem after Different Storage Condition - Nur Rochmah Kumalasari; L R Hanindiyya; M A Setiana (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2020)
Asystasia gangetica (L.) T. Anderson has potency to spread as a forage in plantation area. The aim of this study was to evaluate A. gangetica viability rate with different storage conditions. The research was conducted from March to April 2019 at Laboratory of Forage Science and Pasture Technology, Faculty of Animal Science, IPB University. These research used 600 cutting stems of 70 days old A. gangetica from IPB areas. The experimental design used was a factorial completely randomized and the factors were A: storage material/tools (control, refrigerator, sugar immersion and wax coating) and B: storage time (1, 2, 3, 4, 5, 6 days) with 25 replicates. The measured parameters were physiological cutting stem, length, weight reduces, viability rate and leaves growth. Data were analyzed by ANOVA used software R-3.3.2., then the significant results analyzed by Duncan. The result showed that storage treatments affected cutting stem physiologically, i.e.: color, smell, mold appearance and texture. The most affected was sugar immersion and the less affected was the refrigerator. The length of storage time reduced cutting stem weight. However, the highest viability rate of the cutting stem was in sugar immersion storage. Key words: Asytasia gangetica (L.) T. Anderson, cuttings stem, preservation, storage capacity, viability